Market Segmentation and the `Hump-Shaped' Response of Output to Monetary Policy Shocks - Filippo Occhino (Rutgers University, Department of Economics, 2004)
In the data, after a contractionary monetary policy shock aggregate output decreases over time, with a trough after four to eight quarters. This paper replicates the `hump-shaped' response of output with a segmented markets model where part of the households are excluded from financial markets. A contractionary monetary policy shock is modeled as an unanticipated increase in the short-term nominal interest rate. Since households and firms need cash-in-advance to purchase consumption and hire labor, an increase in the nominal interest rate discourages the households' consumption demand and labor supply, and the firms' labor demand. In a benchmark full participation model, the effect is strongest in the impact period, and decays over time. When markets are segmented, however, the shock has an additional liquidity effect, increasing the real interest rate above fundamentals, and decreasing the growth rate of the participants' labor supply. As a result, the response of the aggregate labor and output has a trough several quarters after the shock. The model is able to replicate the sign, the magnitude and the persistence of the responses of output, money, prices and interest rates. It can generate a positive response of the real interest rate together with a negative response of the output growth rate.
Keywords: E52; 330; limited participation; segmented markets; hump-shaped delayed response; monetary policy shocks; persistence; Marktsegmentierung; Geldpolitik; Schock; Cash-in-Advance-Modell; Arbeitsangebot